An analytics approach to adaptive maturity models using organizational characteristics - Thijs Baars; Frederik Mijnhardt; Kevin Vlaanderen; Marco Spruit (Decision Analytics, 2016)
Ever since the first incarnations of maturity models, critics have voiced several concerns with these frameworks. Indeed, a lack of model fit and oversimplification of the real world can be attributed to the rigidity of these models, which assumes that each organization that uses the framework is equal. This research investigates this fundamental rigidity from an analytics perspective, analysing in casu a focus area maturity matrix targeted at information security. The results show that organizational characteristics influence the maturity framework both in parts and as a whole significantly, concluding that current maturity frameworks have a poor model fit and advising that a maturity framework should account for the differences between the characteristics of their target organizations.
Keywords: 330; Information security; SME; Organizational characteristics; ISFAM; Maturity model; Decision analytics